1994
DOI: 10.1111/j.1751-0813.1994.tb06153.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the epidemiology of bovine ephemeral fever in South Korea and south‐western Japan

Abstract: Bovine ephemeral fever (BEF) outbreaks were investigated in South Korea and Japan from 1953 to 1991, retrospectively. The epidemics occurred contemporaneously several times; particularly, those of 1988 and 1991. The initial outbreaks in the Fukuoka Prefecture, Japan, in 1988 and 1991 occurred about 1 month after those in Korea. Meteorological analysis showed that a low-level jet stream through Jeonnam Province in Korea struck the Fukuoka Prefecture of Japan during the epidemic. The BEF epidemics of Fukuoka Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 6 publications
0
19
0
2
Order By: Relevance
“…(A) Frequency of the occurrence categorized by the mean neutralizing antibody titers of the districts; (B) frequency of occurrence categorized by percentages of the sampled animals with titer lower than 1:32. Shirakawa et al (1994) that the BEF outbreaks in Fukuoka, Japan in 1988 and 1991 may have originated from viral strains that were involved in the earlier Korean outbreaks. Moreover, three BEF epizootics in Taiwan in the last century, namely the 1967, 1983-1984, and 1989-1990 epizootics, roughly coordinated with the 1966, 1983, and 1987 Chinese epizootics that ruined cattle in many provinces (Zheng and Qiu, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…(A) Frequency of the occurrence categorized by the mean neutralizing antibody titers of the districts; (B) frequency of occurrence categorized by percentages of the sampled animals with titer lower than 1:32. Shirakawa et al (1994) that the BEF outbreaks in Fukuoka, Japan in 1988 and 1991 may have originated from viral strains that were involved in the earlier Korean outbreaks. Moreover, three BEF epizootics in Taiwan in the last century, namely the 1967, 1983-1984, and 1989-1990 epizootics, roughly coordinated with the 1966, 1983, and 1987 Chinese epizootics that ruined cattle in many provinces (Zheng and Qiu, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…Although previous BEF epizootics spread widely in mainland Japan [7, 12, 15], the areas affected in 2015 were quite limited. The affected area in the mainland region did not have a high density of cattle herds.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that the origin of the BEFV was the same in two epizootic areas that were 100 km apart. The long-distance transport of infected vectors by wind has been considered for past BEF epizootics [2, 5, 6, 12, 15]. Estimation of the potential source of the infected vectors in the 2015 epizootic should be conducted by using atmospheric dispersal models in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports indicated that outbreaks of ruminant arboviral diseases frequently occurred in this region, and then spread to areas further east and north [5,6,13,16]. Therefore, better knowledge of the distribution and seasonal abundance of vectors and the sensitive detection of arbovirus incursion in Kyushu are needed.…”
mentioning
confidence: 99%